The concept of active site in heterogeneous catalysis - Vogt, Charlotte; Weckhuysen, Bert M. (Nature reviews. Chemistry, 2022)
Catalysis is at the core of chemistry and has been essential to make all the goods surrounding us, including fuels, coatings, plastics and other functional materials. In the near future, catalysis will also be an essential tool in making the shift from a fossil-fuel-based to a more renewable and circular society. To make this reality, we have to better understand the fundamental concept of the active site in catalysis. Here, we discuss the physical meaning — and deduce the validity and, therefore, usefulness — of some common approaches in heterogeneous catalysis, such as linking catalyst activity to a ‘turnover frequency’ and explaining catalytic performance in terms of ‘structure sensitivity’ or ‘structure insensitivity’. Catalytic concepts from the fields of enzymatic and homogeneous catalysis are compared, ultimately realizing that the struggle that one encounters in defining the active site in most solid catalysts is likely the one we must overcome to reach our end goal: tailoring the precise functioning of the active sites with respect to many different parameters to satisfy our ever-growing needs. This article ends with an outlook of what may become feasible within the not-too-distant future with modern experimental and theoretical tools at hand. Heterogeneous catalysis is a diverse and highly interdisciplinary field in chemistry, which is essential in our modern society. This Review highlights how understanding the active site in catalysts will help in their rational design — an essential step in a transition to renewable energy and a circular economy.